Factastic millennium facts - Ash, Russell (New York DK Pub, 1999)
Presents facts, milestones, and key political and cultural events from the year 1000 to the present, highlighting important periods and inventions
Includes index
1
Keywords: Civilization -- History -- Miscellanea -- Juvenile literature; World history -- Miscellanea -- Juvenile literature; Civilization -- History -- Miscellanea; World history -- Miscellanea